Associations between urinary parabens and thyroid hormone homeostasis across trimesters in Taiwanese pregnant women - Po-Chin Huang; Hsi Chen; Pao-Lin Kuo; Hsin-Chang Chen; Wan-Ting Chang; Jung-Wei Chang (Ecotoxicology and Environmental Safety)
Few studies have explored the link between paraben exposure and thyroid hormone homeostasis in pregnant women across trimesters. The present study involved 97 pregnant women from southern Taiwan (2013–2014), and involved measuring urinary methyl, ethyl, propyl, and butyl parabens, as well as serum thyroid hormones and related indices, such as Structure Parameter Inference Approach—Glandular Disturbance [SPINA-GD], and SPINA Global Turnover [SPINA-GT]). Generalized estimating equations (GEE) were applied to examine the effect of longitudinal paraben exposure on thyroid hormone homeostasis. We found that propylparaben and butylparaben levels were associated with increased FT4 levels at the second visit (β = 0.07, p = 0.019; β = 0.08, p = 0.002), respectively. The GEE analysis further supported these associations, indicating the positive association between propylparaben levels and both T3 and FT4 levels over time (β = 0.05, p = 0.019 and β = 0.05, p = 0.026, respectively). Moreover, butylparaben levels were positively associated with FT4 (β = 0.05, p = 0.004) and inversely associated with the T4/FT4 ratio and SPINA-GD values (β = −0.04, p = 0.039 and β = −1.63, p = 0.004, respectively). In the GEE and BKMR analyses, a positive association was observed between PrP or paraben mixtures and T3 and FT4 levels, respectively. The findings of this study indicate that paraben and paraben mixtures have the potential to disrupt thyroid homeostasis by exerting a diverse hormonal effect. Further research is required to substantiate these conclusions in larger sample size populations.